(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The academic pressure and struggle to survive in a cut-throat competitive scenario sometimeslead students to commit suicide. The incident of Alok„s suicide is the anxiety of every student. On surfacelevel one can say that these students enjoy life during the important years of their life then plan to raid inprincipal„s office. So they must be punished. However, one should peep into the matter and one will realizethe brutal system of education where a hectic schedule of course draws the students to frustration anddejection. Cramming the information for getting good grades is not the sign of intelligence.Contemporary education is more syllabus and exam oriented. Bhagat„s success is based on the storieswhich he writes for casual Indians and he completely writes for a contemporary average Indian reader.Though Bhagat discusses most of his subjects which are omni-present yet they first connect to Indians.Bhagat has been criticized for his simplicity of narration by many critics. But if one considers India as awhole set of unit, one will realize that Indians do read but they mostly read in their vernacular. They knowEnglish but most of them have their primary education in their local language. Even in most Englishmedium schools, the standard of English is questionable. In such situation, they prefer to read a bookwith the comfortable language. The common readers who already encounter infinite troubles and stressin their routine life do not want to stretch their stress in reading a language that they are not muchcomfortable with. They might have tried to read the serious and grave writing in English. Even studentsof English literature finds some books of their syllabus belong to a world that has no connection withtheir own world.